Properties of Concrete Containing Foamed Concrete Block Waste as Fine Aggregate Replacement - Khairunisa, Muthusamy; Budiea, Ahmed Mokhtar Albshir; Ahmad Lutfi Fajri, Zaidan; Mohd Hafizuddin, Rasid; Dayang Siti, Hazimmah (IOP Publishing, 2017)
Environmental degradation due to excessive sand mining dumping at certain places and disposal of foamed concrete block waste from lightweight concrete producing industry are issues that should be resolved for a better and cleaner environment of the community. Thus, the main intention of this study is to investigate the potential of foamed concrete block waste as partial sand replacement in concrete production. The foamed concrete waste (FCW) used in this research that were supplied by a local lightweight concrete producing industry. The workability and compressive strength of concrete containing various percentage of foamed concrete waste as partial sand replacement has been investigated. Prior to the use, the foamed concrete waste were crushed to produce finer particles. Six concrete mixes containing various content of crushed foamed concrete waste that are 0%, 10%, 20%, 30%, 40% and 50% were used in this experimental work. Then the prepared specimens were placed in water curing until the testing age. Compressive strength test and flexural strength tests were conducted at 7, 14 and 28 days. The result shows that integration of crushed foamed concrete waste as partial sand replacement in concrete reduces the mix workability. It is interesting to note that both compressive strength and flexural strength of concrete improves when 30% crushed foamed concrete waste is added as partial sand replacement.